Scientific access into Mercer Subglacial Lake: scientific objectives, drilling operations and initial observations. Issue 85 (8th September 2021) - Priscu, John C.; Kalin, Jonas; Winans, John; Campbell, Timothy; Siegfried, Matthew R.; Skidmore, Mark; Dore, John E.; Leventer, Amy; Harwood, David M.; Duling, Dennis; Zook, Robert; Burnett, Justin; et al.
Abstract: The Subglacial Antarctic Lakes Scientific Access (SALSA) Project accessed Mercer Subglacial Lake using environmentally clean hot-water drilling to examine interactions among ice, water, sediment, rock, microbes and carbon reservoirs within the lake water column and underlying sediments. A 0.4 m diameter borehole was melted through 1087 m of ice and maintained over 10 days, allowing observation of ice properties and collection of water and sediment with various tools. Over this period, SALSA collected: 60 L of lake water and 10 L of deep borehole water; microbes >0.2 μm in diameter from in situ filtration of 100 L of lake water; 10 multicores 0.32–0.49 m long; 1.0 and 1.76 m long gravity cores; three conductivity–temperature–depth profiles of borehole and lake water; five discrete depth current meter measurements in the lake and images of ice, the lake water–ice interface and lake sediments. Temperature and conductivity data showed the hydrodynamic character of water mixing between the borehole and lake after entry. Models simulating melting of the 6 m thick basal accreted ice layer imply that debris fall-out through the 15 m water column to the lake sediments from borehole melting had little effect on the stratigraphy of surficial sediment cores.